THE PREDICTION OF TEMPERATURE FIELDS AND STRESSES IN BRIDGE STRUCTURES WITH CLOTHES FROM CLIMATIC AND TECHNOLOGICAL INFLUENCES - Bezbabicheva, O. I.; Rozenfeld, M. V.; Kislov, O. H. (Science and Transport Progress, 2008)
The estimation order of thermal streams on the horizontal and vertical surfaces of bridges is offered. The data of estimation can be used as boundary conditions at determination of the dependence of temperature tensions on climatic factors.